Eusebeia, Thrēskeía and religio: an ethymological analysis of three disputed terms - Petersmann, Hubert (Linguistica, 1993)
While extensive philological research work has made clear the usage and the semantics of the words £UO'E£tcx. (also 0£ocre£tcx.), 0p11crKEta and religio in Greek andl Roman literature, their prehistoric meaning, whence the later sense of these terms has developed, is not transparent at all.1 This is due to the fact that one has not paid too much attention to their etymologies, and thus the problems attached have not yet been definitely solved. By renewing these highly disputed questions the following paper hopes to contribute to a more appropriate understanding of the original sense of the Greek and Latin words for religion, which beyond any doubt belonged to the most important concepts of ancient Hellas and Rome.
Elektronische Reproduktion der Druckausgabe
Gesehen am 05.07.2023